Survival of Allogeneic Hepatocytes Transplanted into the Thymus - Mula, Nieves; Cubero, Francisco J.; Codesal, Javier; de Andrés, Socorro; Escudero, Cristina; García-Barrutia, Socorro; Millán, Isabel; Arahuetes, Rosa M.; Maganto, Paloma (Cells, tissues, organs, 2008)
Background/Aim: Currently, when cell therapy is being considered instead of liver transplantation to treat terminal liver diseases, complete knowledge of the evolution and behavior of ectopically transplanted hepatocytes is a subject of utmost interest in the design of clinical trials. Hepatocytes survive in ectopic locations and have a therapeutic effect in different experimental models. Although it offers remarkable advantages over liver transplantation, hepatocyte transplantation presents several problems, among them the number of cells that can be injected at once and their rejection. Our main objective was to study the survival and functionality of hepatocytes transplanted into the thymus and, secondarily, to test whether the intrathymic transplant could induce any tolerogenic effect. Methods: Hepatocytes from F344 rats were transplanted into thymuses of Gunn rats, half of which received a unique dose of cyclosporine A. The recipients were sacrificed at different times. Light microscopy was performed and bilirubin levels were determined in serum and bile. Results/Conclusions: Transplanted hepatocytes survive for at least 6 weeks in the thymus of allogeneic animals without immunosuppressive therapy. The work provides interesting data about the behavior of hepatocytes injected into this unique ectopic site and shows that the thymus can be used as a recipient organ for cell therapy.